PENERAPAN METODE SQ3R PADA MATERI JURNAL UMUM PERUSAHAAN DAGANG SISWA DI SMK - Ifik Ganda Mana; Maria Ulfah; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to know the result of pretest posttest with using and implementation of Survey, Question, Read, Recite, and Review (SQ3R) method. The purposes of this research were to know: 1. The implication of SQ3R method, 2. The implementation of SQ3R method on general ledger material, 3. The result of before and after using the SQ3R method. The research method used for this study is an experimental research in the form of one group pretest posttest experiment. The source and subject of data derived from 10th grade students of accounting 2, with giving out test sheets of pretest and posttest on general ledger material of merchandising company by implementing of methods treatments are two times. The The result of this research showed there is a different influence between before and after the implementation of Survey, Question, Read, Recite, and Review (SQ3R) method. The average score result of pretest is 52.70 and posttest is 75.00. Keywords: SQ3R Method, General Ledger, Merchandising Company